Diaphragm and secondary battery

By providing an organic coating containing inorganic particles on the organic substrate of the separator, the existing separator has poor dimensional stability and low electrolyte wetting at different temperatures, and a secondary battery with efficient ion transport and long cycle life is achieved.

CN119651058APending Publication Date: 2025-03-18HUIZHOU LIWINON ELECTRONIC TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411964458.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing separators have poor dimensional stability at different temperatures, low electrolyte wetting ability, and low ion transmission efficiency, resulting in attenuation of cycling performance and safety problems of secondary batteries.

Method used

An organic coating containing inorganic particles is provided on an organic substrate. By controlling the size distribution of inorganic particles and the thickness of the coating, the adhesion of the coating and the wettability of the electrolyte are improved, and ion transport efficiency is improved.

Benefits of technology

The dimensional stability of the separator at different temperatures is achieved, the wetting property of the electrolyte and the ion transmission efficiency are improved, the cycle life of the secondary battery is extended, and the safety is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218002330000111
    Figure BDA0005218002330000111
  • Figure BDA0005218002330000121
    Figure BDA0005218002330000121
  • Figure BDA0005218002330000131
    Figure BDA0005218002330000131
Patent Text Reader

Abstract

The invention discloses a diaphragm and a secondary battery, and belongs to the technical field of batteries. According to the diaphragm, an organic coating containing inorganic particles is arranged on an organic substrate, and the size distribution of the inorganic particles is controlled, and meanwhile, the relation between the size of the inorganic particles in the coating and the thickness of the coating is regulated and controlled; the adhesive force of the whole coating can be effectively improved, meanwhile, the diaphragm is good in size stability at different temperatures, good in wettability to electrolyte and high in ion transmission efficiency, and long cycle life and high safety can be achieved when the diaphragm is applied to a secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a diaphragm and a secondary battery. Background Art

[0002] The diaphragm is a key component of the secondary battery. It is mainly located between the positive electrode and the negative electrode, and realizes the reversible transmission of ions under the infiltration of the electrolyte. However, the existing diaphragms are mainly divided into two types. One is an organic diaphragm that has not undergone any processing. This diaphragm has low thermal stability, large dimensional changes at different temperatures, low electrolyte wettability, and insufficient mechanical strength. The other is a modified diaphragm with an additional coating on the basis of an organic substrate. After being modified by using a ceramic coating, the dimensional stability of this type of product is significantly improved, the mechanical strength is also high, and the electrolyte wettability is also improved. However, the ion transmission efficiency of this type of product is reduced, and the adhesion of the coating gradually decreases with the back-and-forth penetration and transmission of ions in the secondary battery and the slow contraction / expansion of the volume, and it begins to fall off, which not only affects the stability of the SEI film / CEI film of the pole piece, but also leads to the attenuation of the cycle performance of the secondary battery, and even safety issues. Summary of the invention

[0003] The purpose of the present application is to overcome the shortcomings of the prior art and provide a diaphragm, wherein an organic coating containing inorganic particles is arranged on an organic substrate, and the size distribution of the inorganic particles is controlled, and the relationship between the size of the inorganic particles in the coating and the coating thickness is regulated at the same time, so that not only the adhesion of the overall coating can be effectively improved, but also the diaphragm has good dimensional stability at different temperatures, good wettability to the electrolyte, and high ion transfer efficiency. When applied to secondary batteries, long cycle life and high safety can be achieved.

[0004] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides a membrane, comprising an organic substrate layer and an organic coating layer;

[0005] The organic coating contains inorganic particles, and the organic coating satisfies: D / H≥5;

[0006] Wherein D μm is the particle size corresponding to when the volume cumulative distribution percentage of the inorganic particles reaches 90%, and D=3-120 μm; H μm is the thickness of the organic coating.

[0007] As an implementation scheme of the present application, the D / H=5-55.

[0008] As an embodiment of the present application, D=10-120 μm.

[0009] As an embodiment of the present application, H=0.5-5 μm.

[0010] As an embodiment of the present application, the surface density of the organic coating is 1.3 to 1.65 g / m 2 .

[0011] As an embodiment of the present application, the mass content of the inorganic particles in the organic coating is 10 to 50%.

[0012] As an embodiment of the present application, the organic coating includes an organic polymer, and the organic polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride based copolymer, polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, acrylate copolymer, and polymethyl methacrylate.

[0013] As an embodiment of the present application, the inorganic particles include at least one of needle-shaped particles and rod-shaped particles.

[0014] As an embodiment of the present application, the chemical composition of the inorganic particles includes at least one of silicon dioxide, barium titanate, aluminum oxide, potassium titanate, barium metatitanate, silicon dioxide, calcium oxide, magnesium oxide, zinc oxide, titanium dioxide, and barium oxide.

[0015] In a second aspect of the present application, the present application provides a secondary battery, comprising the separator described in the present application.

[0016] The beneficial effects of this application are:

[0017] The present application provides a diaphragm, wherein an organic coating containing inorganic particles is arranged on an organic substrate. By controlling the size distribution of the inorganic particles and regulating the relationship between the size of the inorganic particles in the coating and the coating thickness, not only can the adhesion of the overall coating be effectively improved, but the diaphragm also has good dimensional stability at different temperatures, good wettability to the electrolyte, and high ion transfer efficiency. When applied to secondary batteries, long cycle life and high safety can be achieved. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0019] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0020] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0021] The present application is further described below with specific embodiments:

[0022] A separator includes an organic base layer and an organic coating layer;

[0023] The organic coating contains inorganic particles, and the organic coating satisfies: D / H≥5;

[0024] Wherein D μm is the particle size corresponding to when the volume cumulative distribution percentage of the inorganic particles reaches 90%, and D=3-120 μm; H μm is the thickness of the organic coating.

[0025] Traditional ceramic coating modified diaphragms have technical defects such as difficulty in ion transmission and inability to continuously ensure coating adhesion. Although the prior art also introduces organic matter with high ion transmission efficiency and good viscosity into the inorganic coating of the diaphragm, it is hoped that the advantages of the two substances can be synergistically exerted to simultaneously improve the ion transmission efficiency and working stability of the diaphragm, so that the diaphragm can achieve higher secondary battery rate performance and cycle performance when used. However, since organic matter and inorganic particles themselves have large compatibility and dispersibility problems and improper adaptability, the inorganic particles in the coating not only cannot improve the dimensional stability of the diaphragm, but may even cause the diaphragm performance to decay due to particle agglomeration or directional migration, and may even easily cause phenomena such as lithium precipitation when used in secondary batteries, causing safety problems. For this reason, the technical solution of this application uses inorganic particles for compounding in the construction of the diaphragm coating, and the D v90 The D v90The thickness of the coating is compounded and regulated to construct a parameter relationship. The results show that when the coating meets the above-mentioned limitations, while ensuring high wettability of the electrolyte and thus achieving sufficient ion transfer efficiency, the inorganic particles can form a non-completely uniform three-dimensional interlocking network structure with the organic matter in the organic coating. The inorganic particles are both the skeleton of the organic matter and are anchored to each other, effectively reducing the size contraction / expansion amplitude of the organic coating. When the organic coating is constructed on an organic substrate, it can achieve high bonding strength in a manner similar to "anchoring". Even if the organic matter undergoes a certain size change under the influence of external temperature, the organic coating can still achieve strong connection without falling off through the anchoring of the inorganic particles, and ultimately achieve better adhesion at different temperatures. When applied to secondary batteries, it can exhibit long-term cycle stability and safety, and has strong adaptability to the working environment temperature.

[0026] In some embodiments, the D / H=5-55.

[0027] Specifically, the D / H is a range value of one or any two of 5, 8, 10, 12.5, 15, 18, 20, 22, 25, 28, 30, 32, 35, 40, 45, 50, 55.

[0028] In some embodiments, the D / H=20-45.

[0029] In the present application, the thickness of the organic coating of the diaphragm not only affects the ion transmission efficiency, but also directly affects the distribution of inorganic particles and the bonding strength with organic matter. v90 It will directly affect the volume change amplitude of the organic coating due to changes in the external ambient temperature and the anchoring strength of the organic coating to the organic substrate. When the thickness of the organic coating in the diaphragm and the size relationship of the inorganic particles are selected within the above preferred range, the stability and electrochemical performance of the diaphragm when applied to secondary batteries are better.

[0030] In some embodiments, D=10-120 μm.

[0031] Specifically, the D=10μm, 11μm, 12μm, 15μm, 18μm, 20μm, 22μm, 25μm, 28μm, 30μm, 35μm, 40μm, 45μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, or any two of the range values.

[0032] In the technical solution of this application, the D of the inorganic particles v90The test was conducted in the following manner: the diaphragm was pyrolyzed by heating in an air environment, with a cut-off temperature of 500°C. The mass of the diaphragm was observed in real time. After the weight was constant, the ash was taken to wash and separate the inorganic particles with water. The separated inorganic particles were then quantified using a laser particle size analyzer. v90 Test.

[0033] In some embodiments, D=18-85 μm.

[0034] Inorganic particles in organic coatings v90 As the organic coating is constantly changing, the looseness of the three-dimensional interlocking network structure varies, and the ion conduction efficiency is also different; on the other hand, the size of the inorganic particles will directly affect the bonding strength between the organic coating and the organic substrate of the diaphragm. If the particle size is large, it may even damage the particles on the surface of the electrode when assembled with the electrode to prepare a secondary battery, affecting the electrochemical performance and even safety of the secondary battery. If the particle size is small, it may partially fall off due to the volume change of the organic matter when the secondary battery is working, which also affects the electrochemical performance of the secondary battery. When the size of the inorganic particles is preferably within the above range, the application effect of the corresponding diaphragm is better.

[0035] In some embodiments, H=0.5-5 μm.

[0036] Specifically, the H is a range value of one or any two of 0.5μm, 0.8μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm, 3.2μm, 3.5μm, 3.8μm, 4μm, 4.2μm, 4.5μm, 4.8μm, and 5μm.

[0037] In some embodiments, H=1.8-2.5 μm.

[0038] In some embodiments, H=1.9-2.3 μm.

[0039] In some embodiments, the surface density of the organic coating is 1.3 to 1.65 g / m 2 .

[0040] Based on the control design of the size and thickness of the inorganic particles described in the present application, the surface density of the organic coating is moderate, which can take into account the balance of ion transmission, coating adhesion and electrolyte wettability.

[0041] In some embodiments, the mass content of the inorganic particles in the organic coating is 10-50%.

[0042] Specifically, the mass content of the inorganic particles in the organic coating is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%.

[0043] In some embodiments, the organic coating includes an organic polymer, and the organic polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-based copolymers, polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, acrylate copolymers, and polymethyl methacrylate.

[0044] In some embodiments, the mass ratio of the organic polymer to the inorganic particles is (50:50) to (90:10).

[0045] Furthermore, the mass ratio of the organic polymer to the inorganic particles is (60:40) to (80:20).

[0046] By adjusting the content of organic polymer in the organic coating, the size and number of micropores in the coating can be further adjusted when constructing the three-dimensional interlocking network structure. It will also affect the overall viscosity of the organic coating, thereby affecting the electrochemical properties of the diaphragm when used in secondary batteries. When the mass ratio of organic polymer to inorganic particles is preferably within the above range, the comprehensive application effect of the diaphragm is better.

[0047] In some embodiments, the inorganic particles include at least one of needle-shaped particles and rod-shaped particles.

[0048] Specifically, the chemical composition of the inorganic particles includes at least one of silicon dioxide, barium titanate, aluminum oxide, potassium titanate, barium metatitanate, silicon dioxide, calcium oxide, magnesium oxide, zinc oxide, titanium dioxide, and barium oxide.

[0049] Specifically, the inorganic particles may also be particles of a specific composite component such as boehmite.

[0050] In the technical solution of the present application, when the inorganic particles are selected to be needle-shaped or rod-shaped particles, their skeleton effect in the organic coating is better. After compounding with the organic polymer, they will form a dendrite-like three-dimensional structure, which can not only effectively improve the overall ion transmission efficiency of the organic coating, but also improve its wettability to the electrolyte, and can achieve better comprehensive performance compared to traditional spherical or ellipsoidal inorganic particles.

[0051] In some embodiments, the inorganic particles have a D v50 =0.5~55μm, D v10 =0.1~3μm.

[0052] In some embodiments, the component of the organic base layer includes at least one of polypropylene and polyethylene.

[0053] In some embodiments, the organic base layer has a thickness of 3 to 20 μm, a porosity of 20 to 50%, an air permeability of 30 to 400 sec / 100 cc, and a melting point of 130 to 160° C.

[0054] It should be noted that the organic base layer in the membrane described in the present application may be a homemade product, or any one of the commercially available common polypropylene base film, polyethylene base film or composite base film.

[0055] In some embodiments, the organic coating layer in the separator is disposed on one side of the organic base layer.

[0056] Specifically, organic coatings are provided on both sides of the organic substrate layer, and the thickness of the diaphragm is 3.5-15 μm.

[0057] In the technical solution of the present application, the thickness H of the organic coating can be tested by the following method: the membrane is cut into sections, the sections are observed under a scanning electron microscope, and the thickness of the organic coatings on both sides of the organic substrate layer is distinguished and tested by image analysis software. Ten test sites are intercepted on each side at the same magnification, and the average value of the measured thickness is calculated. The average value of the thickness of the organic coatings on both sides is then taken as the thickness H of the organic coating.

[0058] In some embodiments, the organic coating layer is disposed on the organic base layer by coating.

[0059] Specifically, the coating includes at least one of gravure coating, extrusion coating, immersion coating, spray coating, spot coating, and wire rod coating.

[0060] The organic coating in the technical solution of the present application can be constructed on the organic base layer by coating methods including but not limited to the above-mentioned types, and is not limited as long as it does not affect the limitations of the membrane on inorganic particles and thickness.

[0061] In some embodiments, the raw materials for preparing the organic coating include inorganic particles, organic polymers and solvents.

[0062] Specifically, the method for preparing the organic coating is: mixing the preparation raw materials, then coating the mixture on an organic substrate layer, and drying the mixture to obtain the organic coating.

[0063] Specifically, the solvent includes at least one of dimethylacetamide, dichloroethane, dimethylformamide, trichloroethane, chloroform, ethyl acetate, sulfolane, dimethyl sulfoxide, N-methylpyrrolidone, chloroform, dichloromethane and acetone.

[0064] Specifically, in the preparation raw materials, the mass content of the solvent is 70-96%.

[0065] A specific embodiment of the present application further provides a secondary battery, wherein the secondary battery includes the separator.

[0066] In some specific embodiments, the secondary battery further comprises a positive electrode sheet, the positive electrode sheet comprises a current collector and a positive electrode material layer, the positive electrode material layer comprises a positive electrode active material, the positive electrode active material includes but is not limited to LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5 At least one of O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2 and lithium nickel cobalt manganese oxide, and the mass content of the positive electrode material in the positive electrode material layer is 90-99%.

[0067] Specifically, the lithium nickel cobalt manganese oxide includes but is not limited to LiNi9Co 0.5 Mn 0.5 At least one of LiNi8Co1Mn1O2, LiNi7Co2Mn1O2, LiNi7Co1Mn2O2, and LiNi6Co2Mn2O2.

[0068] In some embodiments, the positive electrode material layer further includes at least one of a conductive agent and a binder.

[0069] Furthermore, the binder includes at least one of polyvinylidene fluoride, polyvinyl butyral, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, and polyvinyl alcohol.

[0070] Furthermore, the conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0071] In some embodiments, the thickness of the positive electrode material layer is 70 to 150 μm.

[0072] In some embodiments, the secondary battery includes a negative electrode sheet.

[0073] In some embodiments, the negative electrode plate includes a current collector, a negative electrode material layer disposed on the current collector, the negative electrode material layer includes a negative electrode material, and the mass content of the negative electrode material in the negative electrode material layer is 94-98%.

[0074] In some embodiments, the negative electrode material includes at least one of artificial graphite and silicon-doped graphite.

[0075] In some embodiments, the negative electrode material layer further includes at least one of a conductive agent and a binder.

[0076] Further preferably, the binder includes at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl butyral, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, and polyvinyl alcohol.

[0077] Further preferably, the conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0078] In some embodiments, the thickness of the negative electrode material layer is 50 to 150 μm.

[0079] In some embodiments, the secondary battery also includes an electrolyte, the electrolyte includes a lithium salt and a solvent, the lithium salt includes at least one of LiPF6, LiBOB, LiBF4, LiPF6, LiBF4, LiPF6, LiTFSI, LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2, and the solvent includes at least one of EC, PC, EMC, DMC, DEC, THF, 2-MeTHF, TMS, EA, and MP.

[0080] The present invention is further described below with specific examples, which are not to be construed as limiting the scope of the present invention:

[0081] Examples 1 to 3

[0082] A diaphragm and a secondary battery, wherein the preparation method comprises the following steps:

[0083] Preparation of the diaphragm: Commercially available rod-shaped boehmite is used as inorganic particles, polyvinyl formal (McLean CAS63450-15-7) is used as an organic polymer, and DMAC is used as a solvent to prepare a slurry with a solvent mass content of 80%, which is then coated on both sides of a conventional commercially available PE organic substrate membrane with a thickness of 5 μm, a porosity of 36%, and an air permeability of 143 sec / 100 cc by roller coating, and dried to obtain the diaphragm; the parameters of each diaphragm are shown in Table 1.

[0084] Preparation of positive electrode:

[0085] Lithium cobalt oxide is used as the positive electrode active material, and then the material is mixed with a conductive agent acetylene black and a binder polyvinylidene fluoride in a mass ratio of 95:3:2 in an NMP solvent to prepare a slurry, which is then coated on a current collector aluminum foil, dried, cold pressed, and slit to obtain a positive electrode sheet, and the thickness of the positive electrode material layer on the sheet is 100 μm;

[0086] Preparation of negative electrode sheet:

[0087] Artificial graphite, conductive agent acetylene black, binder styrene-butadiene rubber and sodium carboxymethyl cellulose were mixed in water at a mass ratio of 96:1:1.5:1.5 to prepare a slurry, which was coated on the current collector copper foil, dried, cold pressed and striped to obtain a negative electrode sheet. The thickness of the negative electrode material layer on the sheet was 100 μm.

[0088] Preparation of electrolyte:

[0089] The lithium salt LiPF6 and the non-aqueous organic solvent (the mass ratio of ethylene carbonate: diethyl carbonate: propylene carbonate: propyl propionate: vinylene carbonate = 20:30:20:28:2) are prepared in a mass ratio of 8:92.

[0090] Preparation of secondary batteries:

[0091] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order and then wound. The obtained electrode assembly is placed in a packaging shell and injected with electrolyte and packaged to obtain the secondary battery.

[0092] Embodiments 4 to 6

[0093] A separator and a secondary battery, which differ from Examples 1 to 3 only in that:

[0094] Preparation of the diaphragm: commercially available needle-shaped potassium titanate is used as inorganic particles, aramid (Anhui Li Ke BF1300) is used as an organic polymer, and acetone is used as a solvent to prepare a slurry with a solvent mass content of 80%, which is then coated on both sides of a PE organic substrate film by roller coating and dried to obtain the diaphragm; the parameters of each diaphragm are shown in Table 1, and the PE organic substrate film is the same as in Example 1.

[0095] Embodiment 7-8

[0096] A separator and a secondary battery, which are different from those of Examples 1 to 3 only in the parameters for preparing the separator, as shown in Table 1.

[0097] Example 9

[0098] A separator and a secondary battery, which differ from Examples 4 to 6 only in the parameters for preparing the separator, as shown in Table 1.

[0099] Embodiments 10 to 11

[0100] A separator and a secondary battery, which are different from those of Examples 1 to 3 only in the parameters for preparing the separator, as shown in Table 1.

[0101] Example 12

[0102] A separator and a secondary battery, which differ from Examples 4 to 6 only in the parameters for preparing the separator, as shown in Table 1.

[0103] Embodiments 13-14

[0104] A separator and a secondary battery, which are different from those of Examples 1 to 3 only in the parameters for preparing the separator, as shown in Table 1.

[0105] Embodiment 15

[0106] A separator and a secondary battery, which differ from Examples 4 to 6 only in the parameters for preparing the separator, as shown in Table 1.

[0107] Embodiments 16 to 17

[0108] A separator and a secondary battery, which differ from Examples 1 to 3 only in that:

[0109] Preparation of the diaphragm: commercially available needle-shaped calcium carbonate is used as inorganic particles, polyacrylonitrile (Shanghai Yuanye Y69247) is used as an organic polymer, and DMAC is used as a solvent to prepare a slurry with a solvent mass content of 80%, which is then coated on both sides of the PE organic substrate film by roller coating and dried to obtain the diaphragm; the parameters of each diaphragm are shown in Table 1, and the PE organic substrate film is the same as in Example 1

[0110] Embodiments 18 to 20

[0111] A separator and a secondary battery, which are different from those of Examples 1 to 3 only in the parameters for preparing the separator, as shown in Table 1.

[0112] Comparative Examples 1-2

[0113] A separator and a secondary battery, which are different from those of Examples 1 to 3 only in the parameters for preparing the separator, as shown in Table 1.

[0114] Comparative Examples 3-4

[0115] A separator and a secondary battery, which differ from Examples 4 to 6 only in the parameters for preparing the separator, as shown in Table 1.

[0116] Comparative Examples 5-6

[0117] A separator and a secondary battery, which are different from those of Examples 1 to 3 only in the parameters for preparing the separator, as shown in Table 1.

[0118] In Table 1, the D10, D50 and D90 are the particle sizes Dv10, Dv50 and Dv90 of the inorganic particles in the organic coating of the diaphragm in each of the embodiments and comparative examples.

[0119] Table 1

[0120]

[0121]

[0122] Effect Example 1

[0123] In order to verify the effect of the diaphragm obtained by the technical solution of the present application, the diaphragm obtained in each embodiment was subjected to a transverse and longitudinal shrinkage test at high temperature, and the specific method is as follows:

[0124] Instrument: blast oven & electronic image tester;

[0125] Step 1: Cut the diaphragm into strips of 20*10cm according to MD*TD;

[0126] Step 2: Use an electronic image tester to test the length of the initial spline MD*TD, recorded as L M0 and L T0 ;

[0127] Step 3: Place the diaphragm between folded A4 papers and place in a 130℃ forced air oven for 30 minutes;

[0128] Step ④: Take out the diaphragm and measure its MD and TD lengths as L M and L T ;

[0129] Step 5: Calculate S M =(L M0 -L M ) / L M0 *100%;

[0130] S T =(L T0 -L T ) / L T0 *100%.

[0131] Then, the secondary batteries obtained from each embodiment and comparative example were subjected to the following performance tests:

[0132] (1) Room temperature cycle performance test: In an environment of 25°C, the first charge and discharge were carried out, and constant current and constant voltage charging was carried out at a charging current of 0.1C (i.e., the current value at which the theoretical capacity is completely discharged within 10 hours) until the upper limit voltage was 4.3V, and then constant current discharge was carried out at a discharge current of 1C until the final voltage was 2.5V, and the discharge capacity of the first cycle was recorded; then 100 charge and discharge cycles were carried out, and the discharge capacity of the 300th cycle was recorded.

[0133] Cycle capacity retention rate = (discharge capacity of the 300th cycle / discharge capacity of the first cycle) × 100%;

[0134] The test samples were set as 5 groups of parallel samples, and the final test results were calculated as the average value of the 5 groups of parallel samples.

[0135] (2) High temperature cycle performance test: The difference from the test in step (1) is that the test environment temperature is 45°C and the number of cycles is 100 times.

[0136] (3) Safety test: Each secondary battery was first charged to 4.3 V at a rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 s. It was then discharged at a rate of I1C for 10 s, and the voltage V1 at the end of the discharge was recorded. It was then discharged at a rate of I2C for 1 s, and the voltage V2 at the end of the discharge was recorded. Then, DCR = |V1-V2| / (I2-I1), where I1 is 0.2C and I2 is 1C.

[0137] The test results are shown in Table 2.

[0138] Table 2

[0139]

[0140]

[0141] It can be seen from Table 2 that the diaphragm in the secondary battery of the present application has excellent dimensional stability under heat treatment. In general, the transverse shrinkage rate of the diaphragm in each embodiment product does not exceed 20%, and the longitudinal shrinkage rate does not exceed 18.5%. At the same time, based on the coating regulation set on the diaphragm, high electrolyte wettability and high ion transmission efficiency can be achieved after being applied to the secondary battery. After the secondary battery is cycled 300 times at room temperature, the cycle capacity retention rate can reach more than 90%. In a high temperature environment, the product also has ideal electrochemical performance and safety performance. After 100 cycles at 45°C, the products of each embodiment have a The capacity retention rate can still reach more than 90%, and the DCR growth rate is low; in contrast, the products described in Comparative Examples 1 to 4 are based on the improper relationship between the inorganic particles and the coating thickness in the diaphragm coating, which results in the diaphragm being unable to maintain good dimensional stability under a heating environment. Under the same test, the lateral shrinkage rate and the longitudinal shrinkage rate both exceed 20%. Although it can still maintain good cycle stability at room temperature after being applied to secondary batteries, after 100 cycles at 45°C, the capacity retention rate of the secondary battery is less than 90%, and the DCR growth rate can reach up to about twice that of the embodiment product. In addition, the size of the inorganic particles in the diaphragm coating described in Comparative Examples 5 and 6 is too large or too small, and it is also difficult to achieve good thermal stability. The performance of the product is also low after being applied to secondary batteries.

[0142] According to the test results of each secondary battery in Examples 1 to 17, it can be seen that when constructing the diaphragm coating, the thickness of the coating, the size of the inorganic particles set on the coating and the ratio of the two will directly affect the thermal stability and ion / electron conduction efficiency of the product. When D / H is in the range of 20 to 45, or a more moderate coating thickness and inorganic particle size are selected: preferably, D is in the range of 18 to 85 μm, and / or H is in the range of 1.9 to 2.3 μm, based on the "anchor" effect of the inorganic particles and the full compatibility of the inorganic particles with the organic polymer, the diaphragm can achieve better wettability, thereby achieving higher ion / electron conduction efficiency, and the diaphragm coating has better bonding strength, the overall thermal stability of the diaphragm is better, and the electrochemical performance at high temperature is better.

[0143] According to the comparison between Example 3 and Examples 18 to 20, it can be seen that the change in the ratio of organic polymers and inorganic particles on the diaphragm can further adjust the size and number of micropores in the coating when constructing the three-dimensional interlocking network structure, and will also affect the overall viscosity of the organic coating, thereby affecting the electrochemical properties of the diaphragm when applied to secondary batteries. When the ratio of the two is further preferably in the range of (60:40) to (80:20), the electrochemical performance of the secondary battery is better.

[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of this article rather than to limit the scope of protection of this article. Although the present application is described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of this article can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of this article.

Claims

1. A diaphragm, characterized in that: including an organic base layer and an organic coating; The organic coating contains inorganic particles, and the organic coating satisfies: D / H≥5; Wherein D μm is the particle size corresponding to when the volume cumulative distribution percentage of the inorganic particles reaches 90%, and D=3-120 μm; H μm is the thickness of the organic coating.

2. The diaphragm according to claim 1, characterized in that: The D / H=5-55.

3. The diaphragm according to claim 1, characterized in that: The D=10-120 μm.

4. The diaphragm according to claim 1, characterized in that: The H=0.5-5 μm.

5. The diaphragm according to claim 1, characterized in that: The surface density of the organic coating is 1.3 to 1.65 g / m 2 .

6. The diaphragm according to claim 1, characterized in that: The mass content of the inorganic particles in the organic coating is 10-50%.

7. The diaphragm according to claim 1, characterized in that: The organic coating comprises an organic polymer, and the organic polymer comprises at least one of polyvinylidene fluoride, a polyvinylidene fluoride-based copolymer, polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, an acrylate copolymer, and polymethyl methacrylate.

8. The diaphragm according to claim 1, characterized in that: The inorganic particles include at least one of needle-shaped particles and rod-shaped particles.

9. The diaphragm according to claim 8, characterized in that: The chemical composition of the inorganic particles includes at least one of silicon dioxide, barium titanate, aluminum oxide, potassium titanate, barium metatitanate, silicon dioxide, calcium oxide, magnesium oxide, zinc oxide, titanium dioxide, and barium oxide.

10. A secondary battery, characterized in that: A diaphragm comprising any one of claims 1 to 9.

Citation Information

Cited By

  • Separator and secondary battery

    WO2026143990A1